2003
DOI: 10.1080/10550490390201399
|View full text |Cite
|
Sign up to set email alerts
|

Compliance to Supervised Disulfiram Therapy: A Comparison of Voluntary and Court-Ordered Patients

Abstract: We hypothesized that court mandate would significantly enhance compliance with supervised disulfiram therapy. We conducted a twelve-week prospective study of outpatient compliance with court-ordered, monitored disulfiram treatment as compared to voluntary, monitored treatment. The court ordered group (n=19) was significantly more compliant than the voluntary group (n=22). Legally mandated subjects attended an average of 87% (+/-21%) of scheduled visits, versus 42% (+/-35%) for the group without court order. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 0 publications
1
14
1
Order By: Relevance
“…Consistent with prior research (Glass & Marlowe, 1994;Martin et al, 2003;Schnoll, Goldstein, Antes, & Rinella, 1980), evidence indicated that court-mandated substance users were significantly more likely to remain in treatment compared to those voluntarily receiving treatment. Although there was no significant differences in treatment dropout between the ASPD and non-ASPD substance users, an interaction was evident such that dropout was more likely among ASPD patients voluntarily receiving treatment than ASPD patients who were courtmandated to treatment, suggesting that patients with comorbid ASPD and substance dependence who are not court-mandated to treatment are at an increased risk of dropping out of residential substance use treatment.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Consistent with prior research (Glass & Marlowe, 1994;Martin et al, 2003;Schnoll, Goldstein, Antes, & Rinella, 1980), evidence indicated that court-mandated substance users were significantly more likely to remain in treatment compared to those voluntarily receiving treatment. Although there was no significant differences in treatment dropout between the ASPD and non-ASPD substance users, an interaction was evident such that dropout was more likely among ASPD patients voluntarily receiving treatment than ASPD patients who were courtmandated to treatment, suggesting that patients with comorbid ASPD and substance dependence who are not court-mandated to treatment are at an increased risk of dropping out of residential substance use treatment.…”
Section: Discussionsupporting
confidence: 77%
“…Recent research has begun to focus on the ability of traditional substance use treatment settings to retain patients with both ASPD and substance dependence, as treatment length is one of the most consistent predictors of successful substance use outcomes (Gossop, Marsden, Stewart, & Treacy, 2002;Martin et al, 2003;Simpson, Joe, & Brown, 1997). There have been a number of studies suggesting that substance users with comorbid ASPD are at an increased risk for treatment dropout and subsequent return to drug use and criminal behavior (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to other studies documenting improved retention rates when clients who have alcohol and drug problems are mandated into care (Martin, et al, 2003), in the current sample no differences in attrition were found between voluntary and involuntary clients. At the same time, clients who completed the program-whether voluntary or mandatedaveraged significantly more change than those who dropped out (10.8 versus 7.4 points of change, p Ͻ .05).…”
Section: Partners For Change Outcome Management System and Substance contrasting
confidence: 86%
“…In terms of compliance, court-mandated individuals comply more with treatment protocols, such as supervised disulfiram (Antabuse) programs, than nonmandated participants (Martin, Clapp, Alfers, & Beresford, 2004;Martin et al, 2003). In other instances, court-mandated patients have been less compliant with treatment and yet achieved treatment goals at a rate similar to nonmandated patients (Howard & McCaughrin, 1996).…”
Section: Justice System Involvement Treatment Compliance and Duringmentioning
confidence: 95%